Recent advances in defect-engineered transition metal dichalcogenides for enhanced electrocatalytic hydrogen evolution: perfecting imperfections - Tan, Zheng Hao (2023)
Switching to renewable, carbon-neutral sources of energy is urgent and critical for climate change mitigation. Despite how hydrogen production by electrolyzing water can enable renewable energy storage, current technologies unfortunately require rare and expensive platinum group metal electrocatalysts, which limit their economic viability. Transition metal dichalcogenides (TMDs) are low-cost, earth-abundant materials that possess the potential to replace platinum as the hydrogen evolution catalyst for water electrolysis, but so far, pristine TMDs are plagued by poor catalytic performances. Defect engineering is an attractive approach to enhance the catalytic efficiency of TMDs and is not subjected to the limitations of other approaches like phase engineering and surface structure engineering. In this minireview, we discuss the recent progress made in defect-engineered TMDs as efficient, robust, and low-cost catalysts for water splitting. The roles of chalcogen atomic defects in engineering TMDs for improvements to the hydrogen evolution reaction (HER) are summarized. Finally, we highlight our perspectives on the challenges and opportunities of defect engineering in TMDs for electrocatalytic water splitting. We hope to provide inspirations for designing the state-of-the-art catalysts for future breakthroughs in the electrocatalytic HER.